Immunohistochemical expression of MMP–2 and MMP–9 in the brain tissue of sheep naturally infected with Listeria monocytogenes and relationship with cell death in the Listerial encephalitis - Karayigit, Mehmet Önder; Halıgür, Mehmet; Ekici, Mehmet (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Listeria monocytogenes is an intracellular, food–borne bacterium. Silage is an important source of this pathogen causing listeriosis. Listeriosis is an important health problem for both animals and humans in the world. The disease comprises three clinical syndromes: meningoencephalitis, septicemia and metritis with abortion. Encephalitis is frequently observed and the factors that play a role in its pathogenesis are the subject of research. In this study, the immunohistochemical expression of MMP–2 and MMP–9 together with TUNEL staining was investigated in the pathogenesis of meningoencephalitis in sheep naturally infected with L. monocytogenes. The brains of 25 sheep with Listerial meningoencephalitis were used in this study. Brain material from 10 sheep provided from the slaughterhouse was also used as a control. Tissue sections were stained immunohistochemically with L. monocytogenes, MMP–2 and MMP–9 antibodies. Additionally, TUNEL staining was performed to determine apoptosis in the disease. As a result of the study, it was observed that TUNEL staining in neurons and glial cells, MMP–2 and MMP–9 expressions in vascular endothelial cells, inflammatory cells, microglia and especially neurons in the infected brain tissue were significantly increased compared to controls. These results suggested that MMP–2 and MMP–9 play an active role in the neurodegeneration and cell death that occur in Listerial encephalitis.